Love-Based Curriculum Management in Strengthening Students’ Islamic Character in Madrasah Tsanawiyah - Musolin, Muhlil; Sudarmaji, Waluyo (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze the management of a love-based curriculum in strengthening students’ Islamic character at MTs Negeri 5 Kebumen. This research employs a qualitative approach with a case study design. Primary data were obtained directly from key informants, namely the head of the madrasah, the vice principal for curriculum, and teachers at MTs Negeri 5 Kebumen, while secondary data were collected from official documents and relevant literature. Data collection techniques included interviews, observation, and documentation. Data analysis involved data reduction, data display, and conclusion drawing. The researcher conducted a critical analysis by engaging relevant theories and comparing the findings with related studies. The results indicate that the implementation of love-based curriculum management is carried out through four stages: planning, organizing, implementation, and evaluation. In the planning stage, Pancacinta values are integrated into the vision, mission, learning programs, and instructional tools. The organizing stage is conducted through the distribution of teachers’ duties, management of learning schedules, and provision of supportive facilities. The implementation stage is realized through religious habituation programs at the madrasah level and humanistic learning at the classroom level. Meanwhile, the evaluation stage is carried out through formative and summative assessments covering cognitive, affective, and psychomotor aspects. This study finds that the love-based curriculum makes a significant contribution to shaping students’ Islamic character through the integration of compassion values throughout the educational process.